2017
DOI: 10.1177/1359104517707323
|View full text |Cite
|
Sign up to set email alerts
|

Autism and attachment difficulties: Overlap of symptoms, implications and innovative solutions

Abstract: This article explores overlap of symptoms between autism and attachment difficulties and suggests innovative solutions based on formulation. Currently, clinicians express difficulties in differentiating between these conditions contributing to misdiagnosis. Research into the prevalence of attachment difficulties among children with autism often fails to reflect detailed knowledge of attachment theory. Consequently, studies in this area employ questionable modifications to attachment measures and methods of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 62 publications
2
46
0
1
Order By: Relevance
“…However, substantial research has now demonstrated that children with ASD do form attachment bonds to caregivers (Rutgers, Bakermans‐Kranenburg, van Ijzendoorn, & van Berckelaer‐Onnes, ; Teague et al, ), that the sensitivity of the caregiving they receive is equivalent to that observed in dyads of parents and typically developing children (Ijzendoorn, Rutgers, Bakermans‐Kranenburg, et al, ) and that biological factors provide a stronger causal pathway in the development of ASD (Folstein & Rutter, , ). The long‐lasting impact of such conceptualizations has impeded research into relational factors associated with the development of autism, particularly those investigating child–parent interactions (McKenzie & Dallos, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, substantial research has now demonstrated that children with ASD do form attachment bonds to caregivers (Rutgers, Bakermans‐Kranenburg, van Ijzendoorn, & van Berckelaer‐Onnes, ; Teague et al, ), that the sensitivity of the caregiving they receive is equivalent to that observed in dyads of parents and typically developing children (Ijzendoorn, Rutgers, Bakermans‐Kranenburg, et al, ) and that biological factors provide a stronger causal pathway in the development of ASD (Folstein & Rutter, , ). The long‐lasting impact of such conceptualizations has impeded research into relational factors associated with the development of autism, particularly those investigating child–parent interactions (McKenzie & Dallos, ).…”
Section: Introductionmentioning
confidence: 99%
“…The association between sensitive caregiving practices and secure child attachment has mixed support in samples of children with ASD (Ijzendoorn, Rutgers, Bakermans‐Kranenburg, et al, ; Koren‐Karie, Oppenheim, Dolev, & Yirmiya, ), suggesting that the difficulties in social communication characteristic of ASD may pose a challenge for children and parents alike in understanding and predicting each other's behaviour and intent. Further, issues surrounding the similar symptomatology of autism and disorders of attachment present an ongoing challenge for researchers and clinicians alike in determining whether or not the two conditions are related, and how best to differentiate each condition using standardized measures (Davidson et al, ; Green, ; Mayes, Calhoun, Waschbusch, & Baweja, ; McKenzie & Dallos, ; Teague et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that with severe manifestations on the mother's side of anxiety, insensitivity to the child's signals, rigidity, intrusiveness and unpredictability in the interaction, the presence of negative physical contact with the child, as well as irritation, a low level of reciprocity and organization of the interaction process; a large number of different behavioral disorders are noted in a child. Interpreting these results from a systemic point of view, we can conclude that, when faced with the negative manifestations of the parent, the child's anxiety and / or fear intensifies (Belsky, 2005;Cibralic et al, 2018;McKenzie & Dallos, 2017;Rozga et al, 2018). These feelings reduce the quality of their attention, can enhance the desire to avoid, distance themselves from interaction, and also manifest themselves in defiant behavior, the function of which can be to respond to feelings of fear, anxiety or anger.…”
Section: Resultsmentioning
confidence: 93%
“…If concerned and unsure about the referral process, which is understandable as these cases are often very complex, helpful telephone advice for GPs can be gained from the community paediatrician, CAMHS or social services. In secondary care mental health professionals will use observational procedures or clinical interviews to help make the differentiation (Giltaij et al, 2017; McKenzie, 2017). It can be important for secondary care to differentiate between the diagnoses, not only to access the appropriate intervention, but also, potentially, to alter the prognosis.…”
Section: Differential Diagnosesmentioning
confidence: 99%